Qualitative Study on the Implementation of the Pancasila Student Profile Strengthening Project through the Kebolingko Project in Forming the Sciencepreuner Spirit at State Elementary School 3 Gandatapa - Maharani, Dian; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to understand the implementation of the Pancasila Student Profile Strengthening Project (P5) through Kebolingko activities in forming the spirit of a sciencepreneur in students of SD Negeri 3 Gandatapa. A qualitative approach with a case study method was used to explore the process of implementing the project that utilizes school land for growing vegetables of economic value. Data were collected through observation, in-depth interviews, and documentation, then analyzed qualitatively with triangulation techniques. The results of the study showed that the Kebolingko project succeeded in increasing active student participation, fostering an attitude of environmental concern, collaboration, creativity, and independence. In addition, students were able to apply science concepts contextually and develop science-based entrepreneurial skills. This project is in line with the objectives of P5 in forming the character of students who are faithful, independent, creative, and cooperative. The implications of the study emphasize the importance of developing contextual project-based learning to strengthen the profile of Pancasila students and prepare the younger generation to become innovative and environmentally conscious sciencepreneurs.